The VMC Survey – XLII. Near-infrared period–luminosity relations for RR Lyrae stars and the structure of the Large Magellanic Cloud. Issue 1 (31st March 2021) - Cusano, F; Moretti, M I; Clementini, G; Ripepi, V; Marconi, M; Cioni, M-R L; Rubele, S; Garofalo, A; de Grijs, R; Groenewegen, M A T; Oliveira, J M; Subramanian, S; et al.
ABSTRACT: We present results from an analysis of ∼29 000 RR Lyrae stars located in the Large Magellanic Cloud (LMC). For these objects, near-infrared time-series photometry from the VISTA survey of the Magellanic Clouds system (VMC) and optical data from the Optical Gravitational Lensing Experiment (OGLE) IV survey and the Gaia Data Release 2 catalogue of confirmed RR Lyrae stars were exploited. Using VMC and OGLE IV magnitudes we derived period–luminosity ( PL ), period–luminosity–metallicity ( PLZ ), period–Wesenheit ( PW ), and period–Wesenheit–metallicity ( PWZ ) relations in all available bands. More that 7000 RR Lyrae were discarded from the analysis because they appear to be overluminous with respect to the PL relations. The $PL_{K_{s}}$ relation was used to derive individual distance to ${\sim}22\, 000$ RR Lyrae stars, and study the three-dimensional structure of the LMC. The distribution of the LMC RR Lyrae stars is ellipsoidal with the three axis S 1 = 6.5 kpc, S 2 = 4.6 kpc, and S 3 = 3.7 kpc, inclination i = 22 ± 4° relative to the plane of the sky and position angle of the line of nodes θ = 167 ± 7° (measured from north to east). The north-eastern part of the ellipsoid is closer to us and no particular associated substructures are detected and neither any metallicity gradient.